Pendidikan Karakter Integritas Subnilai Kejujuran dalam Gurindam Dua Belas Karya Raja Ali Haji - Nurfadilah, Nurfadilah (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2023)
Education is a process to produce intelligent and noble human resources. Apart from teaching science, students are also prepared to become moral people and responsive to the times instilling characters education can be implemented through appreciation of literary works. One of them is Gurindam Dua Belas by Raja Ali Haji. This research aims to describe the character education value of integrity, the sub-value of honesty. This research is a qualitative research. This research data is written data in the form of arrays containing the character education value of integrity, the sub-value of honesty found in the 12 chapters of Raja Ali Haji's Gurindam Dua Belas in Malay and written in Latin letters. Data was collected and then analyzed using Paul Ricoeur's hermeneutical theory. Analysis is carried out in three stages, namely understanding from symbol to symbol, giving meaning to the symbols, then thinking using the symbols as a starting point. The results of this research show that the sub-value of honesty referred to in the Gurindam Dua Belas text includes honesty to others and to oneself, and even the smallest lie will still be a lie. This advice is still suitable for current conditions so that Gurindam Dua Belas can be a choice of literary work to be appreciated with students in class.